2017
DOI: 10.5812/semj.14961
|View full text |Cite
|
Sign up to set email alerts
|

Does Physical Activity Could Moderate Perceived Wellness of Health Providers?

Abstract: Background: Sufficient levels of physical activity are an issue for health, quality of life, and more importantly for healthcare providers. This study aimed to determine the status of physical activity and its relationship with perceived wellness in healthcare workers. Methods: This study included about 254 health personnel who work in urban health centers in Shiraz. The IPAQ and PWS selfadministered questionnaires were used to collect information. This study was approved by the ethic and council committee of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Participation in physical activity brings people together and provides personal identity, social identity, and a sense of group membership; it also facilitates communication between people and communities without race, gender, culture and age discrimination (Yıldıran & Yetim, 1996). Participation in physical activity has positive effects on self-respect (Chen et al, 2012;Joseph et al, 2014;Yiğitler, 2014), psychological well-being (Edwards, 2006;Garcia et al, 2012;Verner et al, 2017;Wiese et al, 2018), physical and mental health (Cho & Cho, 2011;Park et al, 2017;Ostovarfar et al, 2018;Way et al, 2018); however, the number of people who do not participate in physical activity is quite high worldwide (World Health Organization, 2004). For example, Bauman (2009) collected data from about 53 thousand people across 20 countries and reported that New Zealand, Czech Republic, the USA, Canada and Australia are the countries where participation in physical activity is most prevalent, while the levels of physical activity are remarkably quite low in the remaining countries.…”
Section: Introductionmentioning
confidence: 99%
“…Participation in physical activity brings people together and provides personal identity, social identity, and a sense of group membership; it also facilitates communication between people and communities without race, gender, culture and age discrimination (Yıldıran & Yetim, 1996). Participation in physical activity has positive effects on self-respect (Chen et al, 2012;Joseph et al, 2014;Yiğitler, 2014), psychological well-being (Edwards, 2006;Garcia et al, 2012;Verner et al, 2017;Wiese et al, 2018), physical and mental health (Cho & Cho, 2011;Park et al, 2017;Ostovarfar et al, 2018;Way et al, 2018); however, the number of people who do not participate in physical activity is quite high worldwide (World Health Organization, 2004). For example, Bauman (2009) collected data from about 53 thousand people across 20 countries and reported that New Zealand, Czech Republic, the USA, Canada and Australia are the countries where participation in physical activity is most prevalent, while the levels of physical activity are remarkably quite low in the remaining countries.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Ostovarfar et al found that self-efficacy is effective in altering behaviors associated with physical activity. People who have strong self-efficacy beliefs are more capable of controlling physical and situational problems [ 52 ]. The results of studies show a two-way correlation between self-efficacy and physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies show a two-way correlation between self-efficacy and physical activity. Therefore, studies show that the advantage of physical activity is not limited to its physical effects, but these activities affect all aspects of health [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These people also spend half of their time in the workplace ( 8 ). On the other hand, a healthy and productive workforce is essential to improve the population health and economic growth ( 9 , 10 ). Therefore, changing the workplace to a suitable supportive environment is a proposed solution to health promotion.…”
Section: Introductionmentioning
confidence: 99%